1982
DOI: 10.1002/1097-0142(19820215)49:4<659::aid-cncr2820490411>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Active specific immunotherapy of established micrometastases with BCG plus tumor cell vaccines: Effective treatment of BCG side effects with isoniazid

Abstract: Intradermal vaccinations with Bacillus Calrnette-Gutin (BCG) and viable but nontumorigenic syngeneic hepatocarcinoma cell vaccines were used successfully to treat micrometastatic disease experimentally induced in inbred guinea pigs at 100 times the minimal lethal dose. Several complications have been associated with the use of viable BCC organisms in the treatment of cancer patients and, in this animal model, intradermal administration of BCG uniformly results in severe ulceration and eschar formation at the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The decision to go further from mouse to man was based on two considerations: (i) the urgent need in the clinic for a new post-operative strategy against metastases and (ii) the development in the USA of an autologous live cell tumor vaccine mixed with Bacillus Calmette Guérin (BCG) by Hanna and colleagues [25,26]. …”
Section: Treatment Of Cancer Patients By Autologous Tumor Cell Vacmentioning
confidence: 99%
“…The decision to go further from mouse to man was based on two considerations: (i) the urgent need in the clinic for a new post-operative strategy against metastases and (ii) the development in the USA of an autologous live cell tumor vaccine mixed with Bacillus Calmette Guérin (BCG) by Hanna and colleagues [25,26]. …”
Section: Treatment Of Cancer Patients By Autologous Tumor Cell Vacmentioning
confidence: 99%
“…A series of studies in the guinea pig line 10 hepatocarcinoma model [1][2][3][4][5][6] demonstrated that BCG mixed with autologous tumor cells can induce systemic immunity capable of eliminating a limited disseminated tumor burden when the vaccine is carefully controlled for quality variables. These include the number of tumor cells, ratio of viable BCG organisms to tumor cells, viability of the tumor cells, and the vaccination regimen.…”
Section: Experimental Modelmentioning
confidence: 99%